The Paneleiras of Goiabeiras-Velha and the discourse of traditional know-how: an analysis of socio-state interactions between the Paneleiras, PMV and IPHAN - Marques, Marcelo de Souza (SOCIOLOGIAS, 2024)
The first historical record of the production of ceramic artifacts in Goiabeiras, Vitória-ES, dates back to 1815. However, from the mid-twentieth century onwards, artisans from the northeast began to settle in this same region and to organize new production centers. From the 1980s onwards, Goiabeiras faced two major conflicts: the growing competition for the local cultural market and the action of the State Government in the extraction area for the clay used in the ceramic production. Articulated with the municipality of Vitória and with IPHAN, the Paneleiras began to organize themselves as a political-identity group and elaborate a discourse of cultural legitimacy. We aim to understand the articulation process and the meanings of this discourse. For this, we mobilize as a theoretical-analytical framework the Discourse Theory in Laclau and Mouffe, employing bibliographic research, document analysis, and in-depth interviews. The research showed us that the discourse on “tradition”, as an empty signifier, was sedimented through the articulation, allowing the Paneleiras to occupy a “place” of national prominence.